Hubungan Somatotype dan Asupan Gizi Makro dengan Kebugaran Jasmani Atlet - Zulfah Rahmah; Defriani Dwiyanti; Iswanelly Mourbas; Eva Yuniritha; - Kasmiyetti (Jurnal Gizi, 2020)
Physical fitness is factor to achieve achievement. Based on data of PPLP West Sumatra in 2018 is 30.6% of athletes included in the category less. Some factors that affect fitness are somatotype and nutritional intake. Somatotypes and balanced nutritional intake will support better sports performance This research aims to determine the correlation between somatotype and macronutrient intake with physical fitness.This research was conducted using a cross sectional design. The sampling method using total sampling method with a sample of 37 people. The intake data collection method uses 3x24 hour food recall, the somatotype is determined by the Heart Carter method and the fitness uses a bleep test. The data were analyzed using Chi-square statisticaltests to see the correlation of somatotype with fitness and correlation pearson tests to see the correlation of macro nutrition intake with fitness. The results showed that the average fitness of athletes was 52.12 mL / kg / min. The results showed an average fitness value of 52.12 mL / kg / min and most were fit.. The average value of energy intake is 3471.71 kcal, protein intake of 88.50gr, fat intake is 97.02 gr, carbohydrate intake of 550.1 gr) water intake was 3253.54 ml and most of the intake is good except water. Bivariate results showed that there was no significant relationship between somatotype and fitness but there was a significant relationship between macro nutrient intake and fitness. Further research is needed to find out other factors that affectfitness.Keywords: Fitness; Somatotype; Macronutrient Intake